The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3390/s18124218
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free and Redox Markers-Based Electrochemical Aptasensors for Aflatoxin M1 Detection

Abstract: We performed a comparative analysis of the sensitivity of aptamer-based biosensors for detection mycotoxin aflatoxin M1 (AFM1) depending on the method of immobilization of DNA aptamers and method of the detection. Label-free electrochemical impedance spectroscopy (EIS) and differential pulse voltammetry (DPV) for ferrocene labeled neutravidin layers were used for this purpose. Amino-modified DNA aptamers have been immobilized at the surface of polyamidoamine dendrimers (PAMAM) of fourth generation (G4) or biot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 42 publications
(56 reference statements)
0
11
0
Order By: Relevance
“…Since their discovery ferrocene (Fc) and its derivatives have been proved to be the excellent chemical reagents in organic and organometallic synthesis, electrochemistry, catalysts, and design of new chiral materials . Nowadays, they have wide applications, for example, medicine, electro‐optical devices, modified electrodes and capacitors, biosensors, and protective coating materials …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since their discovery ferrocene (Fc) and its derivatives have been proved to be the excellent chemical reagents in organic and organometallic synthesis, electrochemistry, catalysts, and design of new chiral materials . Nowadays, they have wide applications, for example, medicine, electro‐optical devices, modified electrodes and capacitors, biosensors, and protective coating materials …”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery ferrocene (Fc) and its derivatives have been proved to be the excellent chemical reagents in organic and organometallic synthesis, electrochemistry, catalysts, and design of new chiral materials. [1][2][3][4][5] Nowadays, they have wide applications, for example, medicine, [6,7] electro-optical devices, [8,9] modified electrodes and capacitors, [10,11] biosensors, [12,13] and protective coating materials. [14] Cyclic voltammetry (CV) is perhaps a more versatile electrochemical technique in modern analytical chemistry that can be used for characterizing electroactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…HERE has been extensive research in the area of selfassembled monolayers (SAMs) within the frame of biosensor surface functionalization. [1][2][3] SAMs are twodimensional nanomaterials that form spontaneously on a variety of solid surfaces in a highly ordered fashion, through the process of self-assembly of their molecular components. [4][5][6][7] In particular SAM formation is one of the simplest approaches in achieving thermodynamically stable monolayers through strong chemisorption that is in contrast to Langmuir-Blodgett and other techniques that lead to physisorption and unstable mono or multilayer films.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Currently some of the most widely used SAMs in biosensing are thiols on Au surfaces and alkylsilanes on oxides, due to their relatively straightforward preparation leading to densely packed monolayers. [16] Generally, both types of thiols (R-SH or -C-SH) [14,15] and silanes (R-Si(OH)3) are strong surface anchors leading to chemisorption with the former binding well to metals, such as Au, Ag, Pt and Cu, while the latter binding preferably to surfaces such as SiO2, indium tin oxide (ITO) and TiO2. It is noted that within molecular immobilization chemisorption does not necessarily entail the presence of a full covalent bond, but also refers to charge-transfer (CT) complexes.…”
mentioning
confidence: 99%
“…Latest research showed successful application of aptamer based biosensors (called as aptasensors) for AFM1 determination using label‐free electrochemical impedance spectroscopy (EIS) . In these aptasensors, target interactions of specific aptamer and AFM1 resulted in the changes of the electrode interface detected by variation of the signals of redox probe (mostly ferricyanide ion).…”
Section: Introductionmentioning
confidence: 99%